Lipoprotein (a) level is associated with plaque vulnerability in patients with coronary artery disease: An optical coherence tomography study. (September 2019) - Muramatsu, Yusuke; Minami, Yoshiyasu; Kato, Ayami; Katsura, Aritomo; Sato, Toshimitsu; Kakizaki, Ryota; Nemoto, Teruyoshi; Hashimoto, Takuya; Fujiyoshi, Kazuhiro; Meguro, Kentaro; Shimohama, Takao; Ako, Junya
Abstract: Background: High lipoprotein (a) [Lp(a)] levels are an independent factor for worse prognosis in patients with coronary artery disease (CAD). However, the association between serum Lp(a) level and coronary plaque vulnerability remains to be determined. Methods: A total of 255 consecutive patients with CAD who underwent optical coherence tomography imaging of culprit lesions were included. Patients were divided into 2 groups according to their Lp(a) levels (the higher Lp(a) group [≥25 mg/dL], n  = 87; or the lower Lp(a) group [<25 mg/dL], n  = 168). Results: The prevalence of thin-cap fibroatheroma (TCFA) was significantly higher in the higher Lp(a) group than in the lower Lp(a) group (23% [ n  = 20] vs. 11% [ n  = 19], p  = 0.014). Although the prevalence of TCFA was comparable between the 2 groups among patients with a lower LDL cholesterol (LDL-C) level (<100 mg/dL), TCFA was significantly more prevalent in the higher Lp(a) group than in the lower Lp(a) group (39% [14/36] vs. 10% [5/50], p  = 0.001) among patients with a higher LDL-C level (≥100 mg/dL). Conclusions: A higher Lp(a) level was associated with a higher frequency of TCFA, particularly in patients with a higher LDL-C level. Highlights: High Lp(a) (≥25 mg/dL) was observed in 34% of patients requiring PCI. Higher Lp(a) was associated with the higher prevalence of thin-cap fibroatheroma. High LDL-C enhanced the association between Lp(a) and thin-cap fibroatheroma.